Preoperative echocardiographic evaluation of cardiac systolic and diastolic function in liver transplant recipients with diabetes mellitus: a propensity-score matched analysis - Kwon, Hye-Mee (Anesth Pain Med (Seoul), 2019)
BACKGROUND: Diabetes mellitus (DM) increases risk of heart failure. It has been shown that diabetes leads to DM-cardiomyopathy, characterized by systolic and diastolic dysfunction. Pre-transplant diastolic dysfunction, has been associated with poor graft outcome and mortality. We assessed the hypothesis that end-stage liver disease (ESLD) patients with diabetes (DM-ESLD), have more advanced cardiac systolic and diastolic dysfunction, compared to ESLD patients without diabetes (Non DM-ESLD). METHODS: We retrospectively evaluated preoperative echocardiography of 1,319 consecutive liver transplant recipients (1,007 Non DM-ESLD vs. 312 DM-ESLD [23.7%]) January 2012–May 2016. Systolic and diastolic indices, such as left ventricular ejection fraction, transmital E/A ratio, tissue doppler s’, e’ velocity, and E/e’ ratio (index of left ventricular end-diastolic pressure), were compared using 1:2 propensity-score matching. RESULTS: DM-ESLD patients showed no differences in systolic indices of left ventricular ejection fraction and s’ velocity, whereas diastolic indices of E/A ratio ≤ 1 (49.0% vs. 40.2% P = 0.014), e’ velocity (median = 7.0 vs. 7.4 cm/s, P < 0.001) and E/e’ ratio (10.9 ± 3.2 vs. 10.1 ± 3.0, P < 0.001), showed worse diastolic function compare with Non DM-ESLD patients, respectively. CONCLUSIONS: DM-ESLD patients suffer higher degree of diastolic dysfunction compared with Non DM-ESLD patients. Based on this, careful preoperative screening for diastolic dysfunction in DM-ESLD patients is encouraged, because poor transplant outcomes have been noted in patients with preoperative diastolic dysfunction.